Studying fiscal policy and measuring its monetary effects in the Iraqi economy During the period 2003- 2020 - Dr. Yousef Ali Abd Al-Asadi; Zahraa Hayder Abd Al-Jabar Al-Battat (Genius Journals, 2022)
The rapid developments of fiscal policy, especially in the global economy, and the profound transformations in the financial and banking sectors were among the main factors that affected economic policies from the monetary effects of fiscal policy
Keywords: Developments; global economy; fiscal policy; Commercial banks